A case study on breastfeeding education in Lebanon's public medical school: exploring the potential role of social networks in medical education. Issue 1 (1st January 2018) - Moukarzel, Sara; Mamas, Christoforos; Warstadt, Melissa F.; Bode, Lars; Farhat, Antoine; Abi Abboud, Antoine; Daly, Alan J
ABSTRACT: Background : Limited knowledge, negative beliefs, and lack of sufficient breastfeeding promotion and support by physicians contribute to global suboptimal breastfeeding rates. Formal medical education is well-known to influence future physicians' knowledge, beliefs, and medical practice. However, less understood is the influence of social networks and processes on the exchange and diffusion of knowledge and practices related to breastfeeding.Objectives : We selected the underserved and under-supported public medical school in Lebanon to examine the social side of medical education. Our objectives were to assess knowledge, beliefs, and self-efficacy related to breastfeeding promotion and support among interns and residents. We also examined the social ecosystem surrounding these students concerning the exchange of breastfeeding knowledge.Design : All data were collected during one study visit per participant. First, an interview-administered structured survey was used to assess beliefs, perceived knowledge, basic breastfeeding knowledge, and self-efficacy related to breastfeeding among n  = 70 medical interns and residents. Then, social network data were collected during a semi-structured interview and analyzed using an ego-network approach. All interviews were voice-recorded, transcribed, coded, and thematically analyzed. Descriptive statistics were used to analyze quantitative survey and social network results.Results : Although interns and residents had positive beliefs about breastfeeding benefits, they had limited knowledge and low self-efficacy related to the psychosocial and clinical aspects of breastfeeding promotion and support. They did not seem to have a well-connected professional network around breastfeeding knowledge and practices. Several tended to rely on their informal/non-professional network, such as their mothers, partners, and sisters, for knowledge and practice.Conclusions : Our work using breastfeeding as an exemplary case suggests there is a role for better attending to the beliefs of medical students as well as to the social side of medical education. Future studies can use social network theory to help identify and address influences on medical education outcomes.